THE EFFECT OF GIVING KEDUDUK LEAF EXTRACT (Melastoma malabathricum L.) ON REDUCING BLOOD SUGAR LEVELS IN MALE WHITE RATS (Rattus norvegicus) WITH KIDNEY DYSFUNCTION COMPLICATIONS - Aisa Dinda Mitra; Deny Sutrisno; Oktarani Nadila (Jurnal Endurance, 2025)
Diabetes mellitus is a multifactorial chronic metabolic disorder characterized by increased blood glucose levels due to insufficient insulin production. One of the plants that can be used to reduce blood sugar levels is keduduk leaves (Melastoma malabathricum L.). This study aims to determine the potential of keduduk leaf extract in reducing blood sugar levels in male white rats (Rattus norvegicus) with complications of kidney dysfunction. Methods This study is an experimental study in which rats were induced diabetes using alloxan dose 150 mg/kgBB for 3 days and kidney dysfunction with gentamicin dose 80 mg/kgBB for 7 days. Data were analyzed using Two Way Anova followed by Duncan test. The results showed that the administration of keduduk leaf extract at a dose of 400 mg/kgBB most significantly reduced blood sugar levels in male white rats with complications of kidney dysfunction. The results of creatinine examination after being given the extract showed that there was an effect of kidney complications on the decrease in blood sugar levels in rats, where the decrease in blood sugar levels in the diabetes group with kidney dysfunction complications was smaller than the diabetes group without complications. Keduduk leaf extract can potentially affect kidney function and has adverse side effects, especially on damaged kidney function. Keywords : Alloxan; keduduk leaf extract (Melastoma malabathricum L.); gentamicin; maceration; blood sugar level reduction